Microscopic Understanding of Interfacial Performance and Antifoaming Mechanism of REP Type Block Polyether Nonionic Surfactants - Yifei Zhao; Chunlong Xue; Deluo Ji; Weiqian Gong; Yue Liu; Ying Li (Molecules, 2024)
In many practical applications involving surfactants, achieving defoaming without affecting interfacial activity is a challenge. In this study, the antifoaming performance of REP-type block polymer nonionic surfactant C12EOmPOn was determined, and molecular dynamics simulation method was employed to investigate the molecular behaviors of surfactants at a gas/water interface, the detailed arrangement information of the different structural segments of the surfactant molecules and the inter-/intra-interactions between all the structural motifs in the interfacial layer were analyzed systematically, by which the antifoaming mechanisms of the surfactants were revealed. The results show that the EO and PO groups of REP-type polyether molecules are located in the aqueous phase near the interface, and the hydrophobic tails distribute separately, lying almost flat on the gas/water interface. The interaction between the same groups of EOs and POs is significantly stronger than with water. REP block polyethers with high polymerization degrees of EO and PO are more inclined to overlap into dense layers, resulting in the formation of aggregates resembling “oil lenses” spreading on the gas/water interface, which exerts a stronger antifoaming effect. This study provides a smart approach to obtaining efficient antifoaming performance at room temperature without adding other antifoam ingredients.